Synthesis, structure, EPR studies and up-conversion luminescence of ZnO:Er3+–Yb3+@Gd2O3 nanostructures. Issue 92 (19th September 2016) - Babayevska, N.; Peplińska, B.; Jarek, M.; Yate, L.; Tadyszak, K.; Gapiński, J.; Iatsunskyi, I.; Jurga, S.
Abstract : ZnO:Er 3+ –Yb 3+ @Gd2 O3 nanostructures were obtained by " wet " chemistry methods – the sol–gel technique for the preparation of ZnO and ZnO:Er 3+ –Yb 3+ nanoparticles (NPs), and the seed deposition method for obtaining Gd2 O3 . Abstract : ZnO:Er 3+ –Yb 3+ @Gd2 O3 nanostructures were obtained by " wet " chemistry methods – the sol–gel technique for the preparation of ZnO and ZnO:Er 3+ –Yb 3+ nanoparticles (NPs), and the seed deposition method for obtaining Gd2 O3 . The crystal structure, morphology, phase and elemental composition, resonant microwave absorption of rare earth ions, point defects in the ZnO:Er 3+ –Yb 3+ @Gd2 O3 crystal structure and up-conversion luminescence were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) with energy dispersive X-ray (EDX), X-ray photoelectron spectroscopy (XPS), electron paramagnetic resonance (EPR) spectroscopy, and optical spectroscopy. The crystallization temperature (600 °C) of the Gd2 O3 phase on the ZnO surface was found. As-obtained ZnO:Er 3+ –Yb 3+ NPs (with size ∼7 nm) are highly crystalline and monodispersed. ZnO:Er 3+ –Yb 3+ NPs annealing at 900 °C leads to the formation of highly polydispersed ZnO:Er 3+ –Yb 3+ NPs, covered by a Gd2 O3 shell. The process of the incorporation of the rare earth ions into the ZnO structure, as well as the effect of Gd2 O3 content on the morphology and visible up-conversion (UC) luminescence in ZnO:Er 3+ –Yb 3+ matrices were studied.